A Study on the Relationship Between Religious Orientations and Quality of Life Among Elderly Men Living in Nursing Homes and Those Living With Their Families in Tabriz - Davod Ghaderi; Ali Mostafaee (University of Social Welfare & Rehabilitation Sciences, 2014)
Objectives: The aim of this study was to determine the relationship between religious orientations with quality of life among elderly men living in nursing homes and those living with their families in Tabriz. Methods & Materials: In this sectional descriptive study, a total of 56 elderly men (consisting of 20 men living in nursing home and 36 men living with their families) selected by random cluster sampling. The Quality of life (John & Ware, 2000) and Religious orientation (Allport & Ross, 1967) questionnaires were administered for all the participants. Data were analyzed using Pearson correlation confident and independent T test. Results: Finding showed there were a positive and significant correlations between mental health, general health, social function, physical function and happiness of older men who lived with their families, and their internal religious orientation (P<0.01). There was also a negative and significant correlation between body pain and external religious orientation (P<0.01). In addition, findings in the older men living in nursing homes showed that there were positive and significant correlations between their mental health, general health, social function, physical function, and happiness, and internal religious orientation (P<0.01). There was also indicated a negative and significant correlation between affective role and external religious orientation (P<0.01). The findings showed Quality of life in those living in nursing home was significantly lower than those living with their families. Conclusion: The results confirmed that there is positive relationships between religious orientation and some dimensions of quality of life both, among elderly men living in nursing homes and those living with their families. Those living with their families had better quality of life compared to those who live in nursing homes.